Manajemen Krisis Bumdes Sekapuk Dalam Memulihkan Citra Wisata Setigi Pasca Kasus Penggelapan Aset Desa - Mohammad Teguh Santoso; Tsuroyya (The Commercium, 2026)
Village-Owned Enterprises (BUMDes) play an important role in improving the village economy through the management of local potential, making organizational sustainability highly dependent on public trust. A conflict involving the former Head of Sekapuk Village triggered a crisis that led to a decline in public trust toward BUMDes Sekapuk and the image of Setigi Tourism as one of the village's main attractions. This study aims to analyze the crisis management strategies implemented by BUMDes Sekapuk in restoring its organizational image after the crisis. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using W. Timothy Coombs’ Situational Crisis Communication Theory (SCCT). The findings reveal that BUMDes Sekapuk implemented various crisis management strategies, including a family-oriented approach, open deliberation forums, mediation processes, improvements in organizational governance, and the rebranding of Setigi Tourism into Sekapuk Smartland. These efforts reflected the application of diminish, rebuild, and bolstering strategies aimed at reducing the impact of the crisis, improving relationships with the community, and rebuilding public trust and organizational image. The study concludes that these strategies contributed significantly to the gradual recovery of BUMDes’ image and the reputation of village tourism.